2017
DOI: 10.1093/jac/dkx453
|View full text |Cite
|
Sign up to set email alerts
|

Italian nationwide survey on Pseudomonas aeruginosa from invasive infections: activity of ceftolozane/tazobactam and comparators, and molecular epidemiology of carbapenemase producers

Abstract: Ceftolozane/tazobactam exhibited potent in vitro activity against P. aeruginosa causing invasive infections in Italy. Carbapenemase production was the most common mechanism of resistance to ceftolozane/tazobactam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 45 publications
3
41
0
1
Order By: Relevance
“…All of the strains in our study were positive for carbapenemase production. Similar to results reported in the literature, we believe this may be responsible for the high C/T and CZA resistance rates in our study [21][22][23][24] . However, the inability to determine carbapenemase type or carbapenemase resistance genes was the major limitation of our study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All of the strains in our study were positive for carbapenemase production. Similar to results reported in the literature, we believe this may be responsible for the high C/T and CZA resistance rates in our study [21][22][23][24] . However, the inability to determine carbapenemase type or carbapenemase resistance genes was the major limitation of our study.…”
Section: Discussionsupporting
confidence: 92%
“…In another study, resistance to C/T in strains producing VIM-2 carbapenemase was found to be 55%, and this high resistance rate was attributed to the fact that the antibiotic does not inhibit Ambler class B carbapenemases [2] . Giani et al [21] detected carbapenemase production in 56.5% of C/T resistant P. aeruginosa strains, while 5.1% of all Pseudomonas strains produced carbapenemase. Among the carbapenemase-producing strains, the rate of bla VIM production was highest at 66.6%, followed by bla IMP at 25%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. aeruginosa izolatları için EUCAST ve CLSI kriterleri aynı olup, MİK değeri ≤4 mg/l olanlar duyarlı, >4 mg/l olanlar dirençlidir [16,17] . Seftolozan/ tazobactam'ın E. coli, K. pneumoniae ve P. aeruginosa izolatlarındaki etkinliğinin değerlendirildiği önde gelen in vitro çalışmalar Tablo 2'de sunulmuştur [5,[16][17][18][19][20][21] . Antibiyotik özellikle P. aeruginosa izolatlarına karşı yüksek aktivite göstermiş olup, %84,4-99 oranında etkili bulunmuştur.…”
Section: İn Vitro Etkinlikunclassified
“…For example, a large Italian multicenter study, conducted from September 2013 to November 2014, showed that TOL/TAZ was the most active antibiotic against PA [6]. The authors collected 935 PA strains (related to pneumonia or bloodstream infections), of which 37.2% expressed an MDR phenotype: overall, TOL/TAZ turned out to be activity against 90.9% of PA isolates, followed by amikacin (88.0% susceptibility) [6].…”
Section: Letter To the Editormentioning
confidence: 99%